Case Report: A New Gain-of-Function Mutation of STAT1 Identified in a Patient With Chronic Mucocutaneous Candidiasis and Rosacea-Like Demodicosis: An Emerging Association - Martinot, Martin; Korganow, Anne Sophie; Wald, Mathieu; Second, Julie; Birckel, Elodie; Mahé, Antoine; Souply, Laurent; Mohseni-Zadeh, Mahsa; Droy, Laure; Tarabeux, Julien; Okada, Satoshi; Migaud, Mélanie; et al. (Frontiers in Immunology, 2021)
Purpose: STAT1 mutations leading to a gain-of-function (GOF) are the first cause of Chronic Mucocutaneous Candidiasis (CMC). We describe a patient presenting a new GOF mutation in STAT1 with clinical symptoms consisting of CMC, recurrent pneumoniae and flowering rosacea with ocular involvement in relation to chronic demodicosis. Methods: A genetic analysis by targeted Next Generation Sequencing (DIPAI v.1) exploring the 98 genes most frequently involved in primary immunodeficiencies including STAT1 was performed to identify new mutations underlying STAT1 GOF. Results: NGS (DIPAI panel) identify a new missense mutation in STAT1, c.884C>A (exon 10), T295Y, not previously described. This new genetic mutation was validated using a STAT1 phosphorylation assay. Rosacae was related to Chronic demodocosis illustrated by important Demodex proliferation diagnosed via microscopic examination of cutaneous sample. A review of literature retrieved 20 other cases of STAT1 GOF mutation associated with rosacea, most of these cases had ocular involvement and an early onset. Conclusion: We describe a new STAT1 GOF mutation associated with a phenotype of CMC and rosacea. Rosacea related to chronic demodicosis appears as a novel and important symptom among some individuals with STAT1 GOF mutation.